2019
DOI: 10.3390/su11247117
|View full text |Cite
|
Sign up to set email alerts
|

The Valuation of Grassland Ecosystem Services in Inner Mongolia of China and Its Spatial Differences

Abstract: Economic valuation of grassland ecosystem services is important for protecting and restoring grassland ecosystems. This study aims to investigate Chinese netizens' willingness-to-pay (WTP) for protecting grassland ecosystem services in Inner Mongolia by using the contingent valuation method. The results indicate that 61.55% of respondents expressed a positive WTP. The mean WTP was estimated to be CNY 170.76 (USD 25.11) per person per year. We found that there is a significant spatial difference in respondent's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 37 publications
(47 reference statements)
0
11
0
Order By: Relevance
“…Grasslands of Inner Mongolia in northern China are productive areas of temperate biodiversity, with great economic and ecological importance [ 1 , 2 , 3 ]. Moderate grazing and hay-making have been widely demonstrated to be an optimal use of grassland that maintains high plant diversity and productivity [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Grasslands of Inner Mongolia in northern China are productive areas of temperate biodiversity, with great economic and ecological importance [ 1 , 2 , 3 ]. Moderate grazing and hay-making have been widely demonstrated to be an optimal use of grassland that maintains high plant diversity and productivity [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, this study finds that gender and education level of the tourists and local residents influence their choice preferences and, therefore, deduces that women give more importance to environment conservation (similar to [75,76]) and those with higher education have better awareness of sustainable development (similar to [77,78]). However, this phenomenon does not exist among aquaculture farmers.…”
Section: Discussion On Differences Of Respondentsmentioning
confidence: 55%
“…Education also appears to be crucial in affecting environmental WTP. Highly educated people show higher levels of concern about the environment [77,78]. Therefore, relevant preferential activities can be provided, such as teacher certificate discounts, postgraduate discounts, student discounts and women-related products, etc.…”
Section: Discussion On Differences Of Respondentsmentioning
confidence: 99%
“…Regarding the acceptance of the policy of returning grazing land to grassland, Ning et al found that the willingness to pay for ecological compensation of farmers is of great significance to their grassland ecological protection behavior [30]. Whether farmers are willing to accept the policy will largely affect their grazing behavior.…”
Section: The Direct Influence Of Consciousness On Behaviormentioning
confidence: 99%